Formulation of a combined low saline water and polymer flooding for enhanced oil recovery - Sarmah, S. (Taylor and Francis Ltd., 2022)
The study aims at formulating a new Enhanced Oil Recovery (EOR) slug comprising a synthetic polymer, (Polyacrylamide (PAM)) and a biopolymer, (Xanthan Gum (XG)). In this case, the EOR will be known as XPS, where low saline water flooding was assisted by PAM and XG. The polymer flooding application in the depleted oil fields of Upper Assam Basin has faced a number of challenges, as it was unable to enhance the viscosity of the displacing fluid and reduce the effective permeability of the displacing fluid, which led to the failure of the macroscopic sweep efficiency (ES) of the reservoir. The rheological properties were found to be Non-Newtonian mostly shear thinning and followed the HerschelâBulkley (HB) and Ostwaldâde Waele power law (OWP) models. The appropriate slugs were further flooded in a core flooding. Low saline water flooding followed by polymer flooding increases the overall recovery efficiency. Â© 2022 Informa UK Limited, trading as Taylor & Francis Group.